Aspects regarding tourism business development in the European Union - Geanina Brinză; Gina Ionela Butnaru (CES Working Papers, 2019)
Tourism activities are developed in the field of hospitality and travels, areas of interest both for customers and for the entrepreneurs who meet the customers' travel needs. The efficiency of European tourism arises from diversified tourist services, modernisation of the means of transportation, competitive prices, and quality of the services offered. This research offers an analysis regarding the current state of tourism in the European Union countries and contributes to the improvement of the knowledge regarding the evolution of tourist businesses on the European tourist market, important as decision factors in the future intentions of both consumers and entrepreneurs.
Keywords: 330; businesses; tourism; tourism business; European tourism business; European Union